A Hierarchy of Power: The Place of Patient and Public Involvement in Healthcare Service Development - O'Shea, Alison; Boaz, Annette L.; Chambers, Mary (Frontiers in Sociology, 2019)
Amidst statutory and non-statutory calls for effective patient and public involvement (PPI), questions continue to be raised about the impact of PPI in healthcare services. Stakeholders, policy makers, researchers and members of the public ask in what ways and at what level does PPI make a difference? Patient experience is widely seen as an important and valuable resource to the development of healthcare services, yet there remain legitimacy issues concerning different forms of knowledge that members of the public and professionals bring to the table, and related power struggles. This paper draws on data from a qualitative study of PPI in a clinical commissioning group (CCG) in the UK. The study looked at some of the activities in which there was PPI; this involved researchers conducting observations of meetings, and interviews with staff and lay members who engaged in CCG PPI activities. This paper explores power imbalances when it comes to influencing the work of the CCG mainly between professionals and lay members, but also between different CCG staff members and between different groups of public and lay members. The authors conclude that a hierarchy of power exists, with some professionals and public and lay members afforded more scope for influencing healthcare service development than others - an approach which is reflected in the ways and extent to which different forms and holders of knowledge are viewed, managed and utilised.